2009
DOI: 10.1038/nsmb.1661
|View full text |Cite
|
Sign up to set email alerts
|

Splice site strength–dependent activity and genetic buffering by poly-G runs

Abstract: Pre-mRNA splicing is regulated through combinatorial activity of RNA motifs including splice sites and splicing regulatory elements (SREs). Here, we show that the activity of the G-run class of SREs is ∼4-fold higher when adjacent to intermediate strength 5'ss relative to weak 5'ss, and ∼1.3-fold higher relative to strong 5'ss. This dependence on 5'ss strength was observed in splicing reporters and in global microarray and mRNA-Seq analyses of splicing changes following RNAi against heterogeneous nuclear ribon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
140
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(159 citation statements)
references
References 51 publications
14
140
1
3
Order By: Relevance
“…When located in introns, G-tracts generally act as splicing enhancers 4 while when located in exons, they mainly act as splicing silencers 5 . G-tracts located in introns were recently shown to be able to buffer genetic variations of 5' splice sites by potentially acting as evolutionary capacitors of splicing changes 6 . G-tracts are also abundant downstream of mammalian polyadenylation signals 7 and in 5' and 3' untranslated regions (UTR) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…When located in introns, G-tracts generally act as splicing enhancers 4 while when located in exons, they mainly act as splicing silencers 5 . G-tracts located in introns were recently shown to be able to buffer genetic variations of 5' splice sites by potentially acting as evolutionary capacitors of splicing changes 6 . G-tracts are also abundant downstream of mammalian polyadenylation signals 7 and in 5' and 3' untranslated regions (UTR) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…1). Such G-runs are typical binding sites for members of the hnRNPF/H protein family (Caputi and Zahler 2001;Schaub et al 2007), which have often been found to inhibit splicing when bound to exonic splicing silencers (ESSs) (Chen et al 1999;Buratti et al 2004;Xiao et al 2009;LeFave et al 2011;Huelga et al 2012;Wang et al 2012). To test whether hnRNPF/H proteins bind to the G-run in exon 4i, we performed protein-RNA crosslinking experiments with RNA substrates containing the conserved 48K element and part of the preceding intron (Verbeeren et al 2010).…”
Section: Recognition Of a Highly Conserved Poison Exon By Hnrnpf/h Prmentioning
confidence: 99%
“…To study this, we knocked down hnRNPH1 in HeLa cells by using increasing amounts of an siRNA that efficiently targets hnRNPH1 (Xiao et al 2009). Efficient reduction of hnRNPH1/H2 levels by 40%-75% (with increasing concentration of siRNA against hnRNPH1) was verified by Western blotting and hnRNPH1 mRNA levels by RT-PCR analysis (Fig.…”
Section: Hnrnph1/h2 Knockdown Enhances Exon 4i Activationmentioning
confidence: 99%
“…8 Clustering of G and C repeats in the adjacent downstream intronic sequence probably helps to increase splice site strength, as has been demonstrated for other introns. 9 In fact, mouse Htt and human HTT have > 75% GC content in the first 55 bases downstream of the intron 1 5′-splice site. Similarly upstream, between the CAG repeat and 5′-splice site, there is a tract of > 80% GC bases in mouse Htt and human HTT.…”
Section: Huntingtin Exon 1-intron 1 Junctionmentioning
confidence: 99%